Serum level of Monocyte chemotactic protein 1 (MCP-1), N-terminal brain natural peptide (NT-proBNP) in Patients with Coronary Heart Disease After Nutritional Changes: serum N-terminal brain natural peptide (NT-proBNP) and Monocyte chemotactic protein 1 (MCP-1), - Wang, Zhancheng (Journal of Medical Biochemistry, 2025)
Objective: Serum level of N-terminal brain natural peptide (NT-proBNP) and Monocyte chemotactic protein 1 (MCP-1), in Patients with Coronary Heart Disease after complementary medicine. Methods: 90 elderly patients with coronary heart disease who were hospitalized from January 2023 to December 2024 were selected and divided into two groups based on different treatment methods, with 45 patients in each group. The control group was treated with western medicine alone, while the research group was treated with Baoyuan and Taohong Siwu decoctions in combination on the basis of control group. The improvement of traditional Chinese medicine symptom scores, various blood lipid levels, and serum indicators of cardiac function were compared between two groups before treatment, 1 month, 2 months, and 3 months of treatment. Results Before treatment, two groups have same TCM symptom scores, various blood lipid levels, and various serum indicators of cardiac function (P>0.05). After treating 1 month, 2 months, and 3 months, the scores of chest pain, chest tightness, fatigue, and sweating in the research group were lower (P
Keywords: N-terminal brain natural peptide (NT-proBNP) and Monocyte chemotactic protein 1 (MCP-1). Baoyuan and Taohong Siwu decoctions; Western medicine; Elderly coronary heart disease; LDL-C, TG, TC, HDL-C